Antifungal activity of ethanol and methanol extracts from Ageratum conyzoides L. against Fusarium oxysporum - Phuong, Tran Thi Thu; Trinh, Nguyen Ba Khanh; Ngan, Nguyen Dinh Thao; Quynh, Nguyen Thi Nhu (Plant Science Today, 2025)
Billygoat weed (Ageratum conyzoides L.) is generally distributed in tropical and subtropical regions. This herb not only has activity against a range of crop pests and pathogens but also boasts a rich history of traditional medicinal use across various countries worldwide. Studies of Ageratum conyzoides have provided evidence of the presence of a wide variety of phytochemicals that are capable of demonstrating its pesticidal, antimicrobial properties. Therefore, this study aimed to investigate the impact of various extracts from the billygoat weed on the antifungal activity against Fusarium oxysporum, a fungus that causes diseases for many crops. The billygoat weed powder was extracted with 2 solvents, ethanol and methanol at 4 concentrations (30 %, 50 %, 70 % and 90 %) and the antifungal activity of the extracts was determined by measuring the inhibition of fungal growth diameter at different extract concentrations (0 %, 1 %, 2 %, 4 % and 8 %). The results demonstrate that the E90 and M90 extracts, at a concentration of 8 %, exhibit better antifungal activity compared to the other extracts at the same concentration, with inhibition rates of 87.21 % and 89.77 % respectively. Moreover, when conducting a 2-factor ANOVA analysis, there was an interaction between solvent strength and extract solution concentration on the growth of Fusarium oxysporum. Hence, Ageratum conyzoides has the potential to be applied in the control of some harmful fungi on plants, oriented as biological pesticides.